Looking forward to a general theory on population aging - J.M. Robine; J.P. Michel (Tijdschrift voor Gerontologie en Geriatrie, 2024)
The main theories on population aging based on recent data on human longevity, life expectancy, morbidity changes, disability trends, and mortality decrease are presented and discussed within their own geographic, cultural, socioeconomic, and medical contexts. The complex interactions between all these components do not facilitate trend forecasting of aging population (healthy aging versus disability pandemic).